MD‐based approaches for system health monitoring: a review. Issue 4 (1st July 2017) - Jin, Xiaohang; Wang, Yu; Chow, Tommy W.S.; Sun, Yi
Abstract : Health monitoring of machines and electronic devices as well as their manufacturing processes plays a significant role in improving their safety, reliability, and their effective lifetime. The Mahalanobis distance (MD)‐based approach is a powerful health monitoring method that has recently received more interest from industrial and academic communities. It has been extensively studied and widely applied in many fields since the early 2000s. This study briefly surveys recent developments and implementation issues of the MD‐based approach in system health monitoring. It provides comprehensive references for researchers, highlights relevant papers, and predicts future research trends.